2019
DOI: 10.18632/aging.102538
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of pseudogene/lncRNA-hsa-miR-363-3p-SPOCK2 pathway fuels stage progression of ovarian cancer

Abstract: Objective: Ovarian cancer is one of the most common and lethal cancer types in women. The molecular mechanism of ovarian cancer progression is still unclear.Results: Here, we first reported that expression levels of three genes, GJB2, S100A2 and SPOCK2, were significantly higher in advanced stage than that in early stage of ovarian cancer, and upregulation of them indicated poor prognosis of patients with ovarian cancer. Subsequently, 8, 6 and 20 miRNAs were predicted to target GJB2, S100A2 and SPOCK2, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 50 publications
1
47
0
Order By: Relevance
“…The majority of OV patients always missed the golden opportunity for surgery until the exact diagnosis. Although great improvements have been achieved in therapies for OV patients, the survival of advanced OV patients was unpromising and the prognosis within five years remained disappointing 5 . Therefore, it is critical to get a deep understanding of latent molecular mechanism underlying OV progression.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of OV patients always missed the golden opportunity for surgery until the exact diagnosis. Although great improvements have been achieved in therapies for OV patients, the survival of advanced OV patients was unpromising and the prognosis within five years remained disappointing 5 . Therefore, it is critical to get a deep understanding of latent molecular mechanism underlying OV progression.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we attempted to systematically explore the expression, prognostic value, correlation with TIICs, and potential mechanism of SPOCK2 in LUAD. In recent studies, SPOCK2 has been shown to be highly expressed in ovarian cancer (Lou et al, 2019) and lowly expressed in prostate cancer (Liu et al, 2019). Its expression increases during lung development (Hadchouel et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that TIICs are positively associated with better survival in LUAD, which highlights the importance of TIICs in the clinical outcomes of LUAD patients (Vafadar, 2019). SPARC (osteonectin), cwcv and kazal-like domains proteoglycan 2 (SPOCK2) is known as a secreted protein that is acidic and cysteine-rich, playing a significant role in the development and progression of ovarian cancer, endometrial cancer, and prostate cancer (Liu et al, 2019;Lou et al, 2019;Ren et al, 2019). It was reported that SPOCK2 can prevent viral infection in lung epithelial cells (Ahn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we identi ed some known lncRNAs may participate in high-glucose treated HUVEC. DAPK1-IT1, DAPK1 intronic transcript 1, has proved involved in cancer progression [41,42] , chemotherapy insensitivity [43] , Atherogenesis [44,45] , etc. In our study, we constructed the coexpression subnet of DAPK1-IT1 and function was analyzed with KEGG pathway (Figure 6), found may function with Terpenoid backbone biosynthesis, Steroid biosynthesis, Vitamin digestion and absorption, Protein processing in endoplasmic reticulum, Phagosome, and some of these pathways have been proved to be involved in the occurrence and development of diabetes.…”
Section: Discussionmentioning
confidence: 99%